The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/cncr.27445
|View full text |Cite
|
Sign up to set email alerts
|

Health status of adolescent and young adult cancer survivors

Abstract: BACKGROUND:Adolescents and young adults (AYA) ages 15 to 29 years who are diagnosed with cancer are at risk for long‐term morbidity and mortality associated with treatment of their cancer and the cancer itself. In this article, the authors describe the self‐reported health status of AYA cancer survivors.METHODS:The authors examined 2009 data from the Behavioral Risk Factor Surveillance System, including demographic characteristics, risk behaviors, chronic conditions, health status, and health care access, amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
280
2
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(303 citation statements)
references
References 44 publications
17
280
2
4
Order By: Relevance
“…1,2 Caught between the worlds of pediatric and adult medical providers, young adults with cancer who are 18-39 years of age are less likely to access optimal medical and psychosocial services, compared to other age groups. 3 While the 5-year survival rates for some common young adult malignancies such as thyroid and testicular cancer exceed 80%, the survival rates for diseases such as leukemia remain less than 60%, with survival rates for some solid tumors even lower.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Caught between the worlds of pediatric and adult medical providers, young adults with cancer who are 18-39 years of age are less likely to access optimal medical and psychosocial services, compared to other age groups. 3 While the 5-year survival rates for some common young adult malignancies such as thyroid and testicular cancer exceed 80%, the survival rates for diseases such as leukemia remain less than 60%, with survival rates for some solid tumors even lower.…”
Section: Introductionmentioning
confidence: 99%
“…(Dieluweit et al, 2011) The ability to work has been shown to improve cancer survivors' quality of life, reduce social isolation, and increase self-esteem. Spelten, 2002) A recent study reported that survivors of AYA cancer are significantly more likely to experience disability and unemployment than healthy controls (24% vs. 14%) (Tai et al, 2012); however, it is unclear why this disparity exists and what factors may be associated. into adulthood.…”
mentioning
confidence: 99%
“…5 Adolescent and young adult (AYA) survivors, a substantial and growing population, 6 demonstrate poor adherence to these recommendations, [7][8][9][10] which is alarming given their increased risk for cancer recurrence, long-term health problems, and poor quality of life. [11][12][13][14][15][16][17][18][19][20] While AYA oncology guidelines stipulate that patients should receive nutrition and exercise guidance, 21 there are limited evidence-based interventions tailored for this group and limited literature on how best to deliver health interventions to AYA survivors. 22 Before designing such interventions, consistent with the Intervention Mapping framework, 23,24 it is important first to identify the barriers to and facilitators of survivors' health behaviors.…”
mentioning
confidence: 99%